rewrite to simplify the equation we distribute fractions. distributing 1/5 gives us 1/10p - 4/3 w and distributing 2/5 gives us 3/10 p - 6 2/3w. combine them for w 1/3w - 4/3w= -3/3w = -w. 3/10 p + 1/10p = 4/10p= 2/5p. so the final answer is 2/5p-w.

in the format so i can copy and paste it

3 answers

To simplify the equation, we start by distributing fractions.

First, distributing \( \frac{1}{5} \) gives us: \[ \frac{1}{5}p - \frac{4}{3}w \]

Next, distributing \( \frac{2}{5} \) results in: \[ \frac{3}{10}p - \frac{20}{3}w \]

Now, we combine the \( w \) terms: \[ -\frac{4}{3}w - \frac{20}{3}w = -\frac{24}{3}w = -8w \]

Next, we combine the \( p \) terms: \[ \frac{1}{10}p + \frac{3}{10}p = \frac{4}{10}p = \frac{2}{5}p \]

The final answer is: \[ \frac{2}{5}p - 8w \]

You can copy and paste this structure as needed!

rewritea again

To simplify the equation, we start by distributing the fractions.

  1. Distributing \( \frac{1}{5} \) gives us: \[ \frac{1}{5}p - \frac{4}{3}w \]

  2. Distributing \( \frac{2}{5} \) gives us: \[ \frac{3}{10}p - \frac{20}{3}w \]

  3. Now, combine the \( w \) terms: \[ -\frac{4}{3}w - \frac{20}{3}w = -\frac{24}{3}w = -8w \]

  4. Next, combine the \( p \) terms: \[ \frac{1}{10}p + \frac{3}{10}p = \frac{4}{10}p = \frac{2}{5}p \]

The final simplified expression is: \[ \frac{2}{5}p - 8w \]

Feel free to copy and paste this version!